Ask Question
6 November, 04:16

Solve the system of equations using substitution. 3x + 2y = 7 y = - 3x + 11 (6, - 3) (5, - 4) (6, - 7)

+3
Answers (1)
  1. 6 November, 05:57
    0
    (5, - 4)

    Step-by-step explanation:

    3x + 2y = 7

    y = - 3x + 11

    The second equation is already solved for y, so since y = - 3x + 11, we substitute y in the first equation with - 3x + 11.

    First equation

    3x + 2y = 7

    3x + 2 (-3x + 11) = 7

    3x - 6x + 22 = 7

    -3x + 22 = 7

    -3x = - 15

    x = 5

    Now we use the second original equation and substitute 5 for x. Then we solve for y.

    y = - 3x + 11

    y = - 3 (5) + 11

    y = - 15 + 11

    y = - 4

    Solution: (5, - 4)
Know the Answer?